Assessment of passive cardiovascular implant devices for MRI compatibility - Walsh, Edward G.; Brott, Brigitta C.; Anayiotos, Andreas; Venugopalan, Ramakrishna; Johnson, Vicki Y. (My University, 2008)
Purpose: The increasing popularity of both magnetic resonance angiography and minimally invasive cardiovascular interventional procedures has led to the requirement for the development of implant devices that not only provide for patient safety, but produce minimal artifacts in diagnostic images. The purpose of this paper is to assess and discuss physical principles and ASTM testing standards related to the MRI compatibility of implanted devices. Analysis and review of imaging compatibility and safety of common implants and devices: Standard procedures are described to assess safety and ability to image near implanted stents and heart valves made from different materials and of varying geometry. MRI physical principles, material properties and MR simulations are discussed in the context of estimation of ferromagnetic force, displacement, torque, tissue heating, susceptibility artifacts, and radiofrequency shielding in cardiovascular stents and heart valves during MR imaging. Conclusion: MRI compatibility is a function of both material composition and device geometry. MR-safe devices are available that provide for reduced image artifacts over stainless-steel devices.
Keywords: Cardiovascular system--Diseases; Magnetic resonance imaging; Radio waves; Stent; Valve